Locally advanced primary breast lymphoma: a rare case report - Rafaela Pereira; Luísa Amado Costa; José Eduardo Rosa; Isabel Duarte (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background Primary Breast Lymphoma is a rare manifestation of extranodal non-Hodgkin lymphoma and accounts for less than 1% of all breast malignancies. It is defined by localized involvement of the mammary tissue by lymphomatous infiltrate in the absence of prior extramammary lymphoma and concomitant widespread disease. Case presentation A 46-year-old melanodermic woman was referred to our hospital due to an extensive ulcerated right breast lesion with signs of infection. Imaging studies revealed a large breast tumor invading the chest wall, with cortical disruption of adjacent ribs and associated pleural thickening. Later, it was complicated with a bronchopleural cutaneous fistula. Biopsy of the mass was performed and the histopathologic diagnosis was consistent with breast infiltration by diffuse large B-cell lymphoma. Concurrent widespread lymphomatous disease and preceding extramammary lymphoma were excluded. Firstly, antibiotic therapy was instituted and surgical debridement was performed in order to control the infection. Afterwards, she underwent chemotherapy and local radiotherapy, with radiologic complete response. Conclusions The diagnosis of primary breast lymphoma is challenging because this disease has non-specific symptoms and imaging features. Radio–pathological correlation and exclusion of systemic lymphoma are essential to establish the diagnosis and to minimize potential complications.